Problematika Minat Baca di Kelas VIII SMPN 26 Makassar - Azzahra, Andi Afifah; Sultan, Sultan; Nurhusna, Nurhusna (PPJB-SIP (Perkumpulan Pengelola Jurnal Bahasa dan Sastra Indonesia serta Pengajarannya)., 2025)
This research aims to (1) describe the internal problems of reading interest in class VIII students at SMP Negeri 26 Makassar; (2) describe the external problems of reading interest in class VIII students at SMP Negeri 26 Makassar. The type of research used is qualitative research. Data collection in this research regarding the problems of students' reading interest was carried out by observation, interviews, questionnaires and documentation. Data sources were obtained from students, teachers, library staff and the principal of SMP Negeri 26 Makassar. Data analysis techniques are carried out through data reduction, data presentation, and drawing conclusions. Qualitative data analysis was used to obtain the problematic reading interest of students in class VIII of SMP Negeri 26 Makassar. The results of this research indicate that the problematic reading interest of class VIII students at SMPN 26 Makassar is influenced by internal problems and external problems. Internal problems, include: (1) reading ability, namely students do not have good reading comprehension skills and students lack vocabulary mastery; (2) attitude, namely feeling lazy about reading and feeling bored when reading; and (3) psychological needs, namely feelings of pressure. External problems, include: (1) availability of reading materials, namely the limited number of books/reading materials in the school library and the lack of variety of reading materials owned by students; (2) peer influence, namely the absence of invitations from peers to read and peers rarely engage in reading activities; (3) the role of parents, namely parents who do not carry out reading activites and there is no parental support; (4) the role of teacher, namely teachers rarely use the library as a learning tool for students; and (5) information and communication technology, namely social media and games, as well as films.